12K views

Uploaded by Kamal Fareed

save

You are on page 1of 10

D2 M at hs HL

PAT T ERNS W I T HI N SYST EMS OF LI NEAR EQUAT I ONS.

Consi der t hi s 2 x 2 syst em of l i near equat i ons: x + 2y = 3

2x – y = -4

Exami ni ng t he f i r st equat i on, w e see a pat t er n i n t he const ant s of t he equat i on, i .e. 1 i s t he const ant

pr ecedi ng t he var i abl e ‘ x’ , and 2 pr ecede ‘ y’ and t he equat i on equal s 3. The const ant s have a common

di f f er ence of 1 bet w een t hem:

2 – 1 = 1

3 – 2 = 1

Goi ng f or w ar d f r om t hi s, w e can say t hat t he const ant s i n t he f i r st equat i on bel ong t o an ar i t hmet i c

ser i es w i t h a common di f f er ence of 1. Thi s means t hey f ol l ow t he gener al f or mul a:

U

n

= U

1

+ (n – 1 ) d w her e:

n = number of t he t er m (i .e. f i r st , second, t hi r d, et c)

d = i s t he common di f f er ence i n t he ser i es.

Looki ng at t he second equat i on, w e al so obser ve t hat t he const ant s ar e consecut i ve member s of and

ar i t hmet i c ser i es, t hi s t i me w i t h common di f f er ence of -3:

-1 – 2 = -3

-4 – (-1) = -3

Sol vi ng t he equat i ons si mul t aneousl y:

x + 2y = 3 mul t i ply f i r st equat i on t o el i mi nat e ‘ x’

2x – y = -4

2x+ 4y = 6

- 2x – y = -4 5y = 10

∴ y = 2

Put t i ng i n t he sol ut i on obt ai ned f or y i nt o t he or i gi nal equat i on t o f i nd x:

x + 2(2) = 3

x = 3 – 4 ∴ x = −1

Kamal F Sei f .

D2 M at hs HL

Sol vi ng equat i ons w i t h t he si mi l ar f or mat :

1. 3x + 5y = 7 const ant s have a common di f f er ence (d) of 2

11x + 5y = -1 const ant s have a common di f f er ence of (d) -6

-8x = 8 ∴ x = -1

3(-1) + 5y = 7

5y = 10

∴ y = 2

2. 100x + 200y = 300 common di f f er ence of 100

-12x – 20y = -28 common di f f er ence of -8

M ul t i pl yi ng t he second equat i on by 10 t o el i mi nat e y:

-20x = 20 ∴ x = -1

100(-1) + 200y = 300

200y = 400 ∴ y = 2

2x – y = -4

x + 2y = 3

The sol ut i on of x and y f or t he t w o

equat i ons al so gi ves us t he x and y

coor di nat e of t he poi nt of i nt er sect i on

of t he t w o l i nes.

At t hi s poi nt (-1,2) t he l i nes ar e equal :

Equat i on 1 = Equat i on 2:

af t er r ear r angi ng t he equat i ons,

y =

3-x

2

And y = 2x +4:

At t he poi nt of i nt er sect i on, y =y

Kamal F Sei f .

D2 M at hs HL

3. 87x + 47y = 7 common di f f er ence of -40

29x + 34y = 39 common di f f er ence of 5

M ul t i pl yi ng t he second equat i on by 3 t hi s t i me el imi nat i ng x:

-55y = -110 ∴ y = 2

Put t i ng i n y i n t he f i r st equat i on:

87x + 47(2) = 7

87x = -87 ∴ x = -1

It seems t hat any equat i on w her e t he const ant s f ol l ow an ar i t hmet i c ser i es w i ll give t he answ er f or y as

2 and f or x -1. Thi s suggest s t hat any t w o l i nes w hose equat i ons t hat ar e si mi l ar t o t hese w i l l i nt er sect at

t he same poi nt . Thi s means t hat w e can gener at e a gener al f or mul a f or equat i ons si mil ar t o t hese:

l et t he f i r st t er m of t he f i r st equat i on be P

1

and l et i f have a common di f f er ence of d.

l et t he f i r st t er m of t he second equat i on be U

1

and have a common di f f er ence of c.

t her ef or e t he f i r st equat i on w i l l l ook l i ke: t he second equat i on w i l l l ook li ke:

U

1

x+ (U

1

+ d) y = (U

1

+ 2d) P

1

x + (P

1

+ c) y = (P

1

+2c)

Sol vi ng t he equat i ons:

U

1

x+ (U

1

+ d) y = (U

1

+ 2d) mul t i ply t he f i r st equat i on by P

1

t o el i mi nat e x

P

1

x + (P

1

+ c) y = (P

1

+2c) mul t i ply t he second equat i on by U

1

t o el i mi nat e x

P

1

U

1

x + (P

1

U

1

+ dP

1

) y = (P

1

U

1

+ 2dP

1

) subt r act t he second equat i on f r om t he f i r st one t o

P

1

U

1

x + (P

1

U

1

+ cU

1

) y = (P

1

U

1

+ 2cU

1

) r emove t he x var i abl e.

P

1

U

1

y - P

1

U

1

y + dP

1

y - cU

1

y = P

1

U

1

- P

1

U

1

+ 2dP

1

– 2cU

1

dP

1

y - cU

1

y = 2dP

1

– 2cU

1

y (dP

1

- cU

1

) = 2 (dP

1

- cU

1

) ∴ y = 2

put t i ng i n t he val ue f or y i n t he f i r st equat i on:

U

1

x+ (U

1

+ d) 2 = (U

1

+ 2d)

U

1

x + 2U

1

+ 2d = U

1

+2d

U

1

x = U

1

– 2U

1

+ 2d – 2d

U

1

x = -U

1

∴ x = -1

Kamal F Sei f .

D2 M at hs HL

The r esul t suggest s t hat f or any t w o l i near equat i ons w r i t t en i n t he f or m:

ax + by = c

dx + ey = f

and t her e i s a common di f f er ence i n t he const ant s a, b and c, such t hat :

c-b = b-a

and a common di f f er ence i n t he const ant s d, e and f , such t hat :

f -e = e-d

but :

(f -e) or (e-d) ≠ (c-b) or (b-a) because i f t he common di f f er ence i n t he t w o equat i ons i s t he same, t hi s

w i ll suggest t hat t he t w o l i nes ar e col l i near , and t her ef or e t hey w i l l never i nt er sect , and i t w i l l not be

possi bl e t o sol ve f or x and y.

The r esul t w i l l alw ays be (-1,2)

If w e ext end t hi s t o 3 x 3 syst ems f or i nst ance usi ng t he f ol l ow i ng equat i ons:

x + 2y + 3z =4 (common di f f er ence of 1)

4x + 6y + 8z = 10 (common di f f er ence of 2)

2x + y = -1 (common di f f er ence of -1)

We can sol ve t hi s syst em of equat i on usi ng mat r i ces:

x 1 2 3 4

y 4 6 8 = 10

z 2 1 0 -1

X M = A

To sol ve f or x, y and z w e have t o f i nd t he i nver se of t he mat r i x M , and mul t i pl y i t w i t h A:

X = A M

-1

Use t echnol ogy t o det er mi ne t he i nver se of M :

Thi s i s a si ngul ar mat r i x, t hi s means t he det er mi nant = 0. Ther ef or e t her e ar e ei t her many sol ut i ons f or

x, y and z, or t her e i s no sol ut i on at al l :

Kamal F Sei f .

D2 M at hs HL

It seems t hat al l 3 x 3 syst ems t hat exhi bi t an ar i t hmet i c pr ogr essi on w i l l gi ve a det er mi nant of zer o, i .e.

f or m a si ngul ar mat r i x.

Let t he f i r st t er m of t he f i r st equat i on be U

1

and t he common di f f er ence d

Let t he f i r st t er m of t he second equat i on be P

1

and t he common di f f er ence be c

Let t he f i r st t em of t he t hi r d equat i on of be Q

1

and t he common di f f er ence b

The equat i ons w i l l l ook l ike:

U

1

x + (U

1

+ d)y + (U

1

+ 2d)z = (U

1

+3d)

P

1

x + (P

1

+ c)y + (P

1

+ 2c)z = (P

1

+ 3c)

Q

1

x + (Q

1

+ b)y + (Q

1

+ 2b)z = (Q

1

+3b)

Ar r angi ng t he equat i on i nt o a mat r i x:

X U

1

(U

1

+d) (U

1

+ 2d) (U

1

+3d)

y P

1

(P

1

+ c) (P

1

+ 2c) = (P

1

+ 3c)

z Q

1

(Q

1

+ b) (Q

1

+ 2b) (Q

1

+3b)

Fi ndi ng t he det er mi nant :

U

1

[ (Q

1

+2b)(P

1

+c) – (Q

1

+b)(P

1

+2c)] – (U

1

+d)[ P

1

(Q

1

+2b) – Q

1

(P

1

+2c)] + (U

1

+2d)[ P

1

(Q

1

+b) – Q

1

(P

1

+c)

U

1

(P

1

Q

1

– P

1

Q

1

+ Q

1

c – 2Q

1

c + 2P

1

b - P

1

b +2bc – 2bc)

-- (U

1

+ d)(P

1

Q

1

- P

1

Q

1

+ 2P

1

b – 2Q

1

c)

+ (U

1

+ 2d)(P

1

Q

1

– P

1

Q

1

+ P

1

b – Q

1

c)

2P

1

U

1

b - 2P

1

U

1

b + 2Q

1

U

1

c - 2Q

1

U

1

c + 2Q

1

dc - 2Q

1

dc + 2P

1

bd - 2P

1

bd

= 0.

Thi s show s t hat al l 3 x 3 mat r i ces w i t h ar i t hmet i c pr ogr essi on w i ll have a det er mi nant of 0. Thi s means

t her e i s ei t her a cont r adi ct i on i n t he equat i ons i .e. no def i ni t e answ er , or t her e ar e many answ er s, i .e.

t hey i nt er sect i n a l i ne.

In or der t o f i nd out i f t her e ar e no sol ut i ons w e have t o see i f t her e i s a cont r adi ct i on i n t he equat i ons:

Fi r st t he t hr ee ar e gr ouped i n gr oups of t w o as show n:

Kamal F Sei f .

D2 M at hs HL

U

1

x + (U

1

+ d)y + (U

1

+ 2d)z = (U

1

+3d) M ul t i pl y t he f i r st equat i on by P

1

t o el i mi nat e x

P

1

x + (P

1

+ c)y + (P

1

+ 2c)z = (P

1

+ 3c) M ul t i pl y by U

1

M ul t i pl y by Q

1

t o el i mi nat e x

Q

1

x + (Q

1

+ b)y + (Q

1

+ 2b)z = (Q

1

+3b) M ul t i pl y by P

1

Fi r st t w o equat i ons:

P

1

U

1

x + P

1

U

1

y + P

1

d y + P

1

U

1

z + 2P

1

d z = P

1

U

1

+ 3P

1

d subt r act t he second f r om t he f i r st .

P

1

U

1

x + P

1

U

1

y + U

1

c y + P

1

U

1

z + 2U

1

z = P

1

U

1

+ 3U

1

c

P

1

d y - U

1

c y + 2P

1

d z - 2U

1

c z = 3P

1

d - 3U

1

c

(p

1

d – U

1

c) y + (P

1

d – U

1

c) 2z = (P

1

d – U

1

c) 3

Wi t h t he f i r st t w o equat i ons w e f i nd: Y + 2z = 3

Last t w o equat i ons:

P

1

Q

1

x + P

1

Q

1

y + Q

1

c y + P

1

Q

1

z + 2Q

1

c z = P

1

Q

1

+ 3Q

1

c subt r act t he second f r om t he f i r st .

P

1

Q

1

x + P

1

Q

1

y + P

1

b y + P

1

Q

1

z + 2P

1

bz = P

1

Q

1

+ 3P

1

b

Q

1

c y – P

1

b y + 2Q

1

c z – 2P

1

bz = 3Q

1

c – 3P

1

b

(Q

1

c – P

1

b) y + (Q

1

c – P

1

b) 2z = (Q

1

c – P

1

b) 3

y + 2z = 3

The t w o sol ut i ons show us t hat t her e i s no cont r adi ct i on i n t he t hr ee equat i ons, t hi s means t hat t he

equat i on has many sol ut i ons, i .e. t hey i nt er sect not at a poi nt , but t hey i nt er sect t o f or m a l i ne.

If w e pl ot t he equat i ons: x + 2y + 3z =4

4x + 6y + 8z = 10

2x + y = -1 w e get t he f ol l ow i ng gr aph:

Thi s show s us t hat t he t hr ee equat i ons j oi n t o make a l i ne.

Fol l ow i ng t he equat i on of t he l i ne:

Kamal F Sei f .

D2 M at hs HL

Y + 2z = 3 w hen y=1, z=1, x=-1

w hen y=-1, z=2, x=0

We have t w o poi nt s P

1

(-1, 1, 1) and P

2

(0, -1, 2), w e can use t he t w o poi nt s t o f i nd t he di r ect i on vect or of

t he l i ne. (P

2

– P

1

):

Di r ect i on vect or : 1

-2

1

Ther ef or e w e can say t hat f or a 3 x 3 syst em t hat exhi bi t an ar i t hmet i c sequence, t he t hr ee pl ai ns w i l l

meet t o f or m a l i ne t hat has t he di r ect i on vect or : 1 , or a mul t i pl e of i t . The poi nt on t he l i ne has t o

-2

1

sat i sf y t he equat i on: U

1

x + (U

1

+ d)y + (U

1

+ 2d)z = (U

1

+3d) w her e U

1

i s t he f i r st t er m of t he ar i t hmet i c

ser i es and d i s t he common di f f er ence of t he ser i es.

Part B:

Consi der t hi s 2 x 2 syst em: x + 2y = 4

5x – y =

1

5

Exami ni ng t he equat i ons, t hey exhi bi t a geomet r i c ser ies i n t he const ant s of t he equat i ons.

In t he f i r st equat i on t he const ant s ar e:

1 2 4,

The second const ant i s t w o t i mes t he f i r st , and t he t hi r d i s t w o t i mes t he second. The equat i on exhi bi t s a

geomet r i c ser i es w i t h a common r at i o of 2.

For second equat i on t he const ant s ar e:

5 -1

1

5

The common r at i o i s −

1

5

, i .e. i f w e t ake t he f i r st const ant and mul t i pl y i t by t he common r at i o w e get

t he second const ant and so on.

The equat i ons f ol l ow t he gener al f or mul a U

n

=U

1

r

n-1

w her e:

U

1

i s t he f i r st t er m of t he ser i es

n i s t he t er m number (i .e. f i r st , second, t hi r d, et c)

r i s t he common r at i o

If w e r e-w r i t e t he equat i ons i n t he f or m of y = ax + b:

y =−

1

2

x + 2

y = 5x -

1

5

Kamal F Sei f .

D2 M at hs HL

We see t hat t he const ant s have a common f eat ur e; b i s t he negat i ve i nver se of a, and a i s t he negat i ve

i nver se of b, i .e. t hey ar e negat i ve i nver ses of each ot her . t hi s means i f w e mul t i pl y t he const ant a by b

t he r esul t i s -1:

5 X −

1

5

= -1

−

1

2

X 2 = -1

Sol vi ng t he t w o equat i ons t o get t he val ues f or x and y:

x + 2y = 4

5x – y =

1

5

mul t i ply t he second equat i on by 5 t o si mpl i f y i t :

x + 2y = 4 mul t i ply t he f i r st equat i on by 25 t o el i mi nat e x

25x – 5y = 1

25x + 50y = 100

25x – 5y = 1

55y = 99

y =

99

55

≈ 1.8

pl uggi ng i n t he val ue f or y i n our or i gi nal equat i on:

5x -

9

5

=

1

5

25x – 9 = 1

25x = 10

x =

10

25

≈ 0.4

If w e r epr esent t he l i nes on a gr aph w e can det er mi ne t he poi nt of i nt er sect i on of t he t w o l i nes

(poi nt A): i .e. t he sol ut i on f or x and y.

Kamal F Sei f .

D2 M at hs HL

The sol ut i ons t o t he di f f er ent l i nes can be cal cul at ed usi ng t he gener al f or mul a:

U

1

x +U

1

r y = U

1

r

2

geomet r i c ser i es w i t h f i r st t er m U

1

and common r at i o of r

P

1

x + P

1

v y = P

1

v

2

geomet r i c ser i es w i t h f i r st t er m P

1

and common r at i o of v

P

1

U

1

x + P

1

U

1

r y = P

1

U

1

r

2

mul t i pli ed t he f i r st equat i on by P

1

t o el i mi nat e x

P

1

U

1

x + P

1

U

1

v y = P

1

U

1

v

2

mul t i pli ed t he second equat i on by U

1

t o el i mi nat e x

P

1

U

1

r y - P

1

U

1

v y = P

1

U

1

r

2

- P

1

U

1

v

2

P

1

U

1

y (r – v) = P

1

U

1

(r

2

– v

2

)

y =

( ¡

2

-¡

2

)

( ¡-¡)

=

( ¡-¡) ( ¡+¡)

( ¡-¡)

= (r + v)

w hen w e pl ug i n t he val ue f or y i n our or i gi nal equat i on:

U

1

x + U

1

r (r + v)= U

1

r

2

U

1

x = U

1

r

2

- U

1

r (r + v)

x = r

2

–r (r + v)

x =r

2

–r

2

– r v

x = - r v

To pr ove t he f or mul a f or t he x and y coor di nat es, (f or poi nt F on t he gr aph), t he poi nt of i nt er sect i on f or

t he l i nes:

A:(0.4,1.8)

B:(1,1.5)

C:(-0.1,-0.7)

D:(-0.5,2.25)

E:(0.13,-0.3)

F:(-10,7)

G:( -1.3,5.3)

H:(1,4.8)

I:(2.5,4.5)

Kamal F Sei f .

D2 M at hs HL

y = −

1

2

x + 2 common r at i o (r ) = 2

y = −

1

5

x + 5 common r at i o (v) = 5

Ther ef or e t he poi nt F (- r v, (r + v))

Coor di nat e x= - (5 X 2) = -10

Coor di nat e y= 5 +2 = 7

Poi nt F(-10, 7) as seen f r om t he gr aph.

The same f or mul a can be used t o cal cul at e t he di f f er ent poi nt s of i nt er sect i on f or t he di f f er ent gr aphs.

y =y x + 2y = 3 Solving equations with the similar format: 1. 100x + 200y = 300 -12x – 20y = -28 common difference of 100 common difference of -8 Multiplying the second equation by 10 to eliminate y: -20x = 20 100(-1) + 200y = 300 200y = 400 ∴ x = -1 ∴y=2 .2) the lines are equal: Equation 1 = Equation 2: after rearranging the equations. At this point (-1. D2 Maths HL 2x – y = -4 The solution of x and y for the two equations also gives us the x and y coordinate of the point of intersection of the two lines. 3x + 5y = 7 11x + 5y = -1 -8x = 8 3(-1) + 5y = 7 5y = 10 ∴y=2 ∴ x = -1 constants have a common difference (d) of 2 constants have a common difference of (d) -6 2. = And y = 2x +4: At the point of intersection.Kamal F Seif.

cU1) = 2 (dP1 . D2 Maths HL 3. This suggests that any two lines whose equations that are similar to these will intersect at the same point. the second equation will look like: P1 x + (P1 + c) y = (P1 +2c) P1U1 x + (P1U1 + dP1) y = (P1U1 + 2dP1) P1U1 x + (P1U1 + cU1) y = (P1U1 + 2cU1) P1U1 y .P1U1 + 2dP1 – 2cU1 dP1 y .P1U1 y + dP1 y .cU1) putting in the value for y in the first equation: U1 x+ (U1 + d) 2 = (U1 + 2d) U1 x + 2U1 + 2d = U1 +2d U1 x = U1 – 2U1 + 2d – 2d U1 x = -U1 ∴ x = -1 ∴y=2 .cU1 y = P1U1 .Kamal F Seif.cU1 y = 2dP1 – 2cU1 y (dP1 . 87x + 47y = 7 29x + 34y = 39 common difference of -40 common difference of 5 Multiplying the second equation by 3 this time eliminating x: -55y = -110 ∴y=2 Putting in y in the first equation: 87x + 47(2) = 7 87x = -87 ∴ x = -1 It seems that any equation where the constants follow an arithmetic series will give the answer for y as 2 and for x -1. let the first term of the second equation be U1 and have a common difference of c. This means that we can generate a general formula for equations similar to these: let the first term of the first equation be P1 and let if have a common difference of d. therefore the first equation will look like: U1 x+ (U1 + d) y = (U1 + 2d) Solving the equations: U1 x+ (U1 + d) y = (U1 + 2d) P1 x + (P1 + c) y = (P1 +2c) multiply the first equation by P1 to eliminate x multiply the second equation by U1 to eliminate x subtract the second equation from the first one to remove the x variable.

The result will always be (-1. b and c.2) If we extend this to 3 x 3 systems for instance using the following equations: x + 2y + 3z =4 4x + 6y + 8z = 10 2x + y = -1 (common difference of 1) (common difference of 2) (common difference of -1) We can solve this system of equation using matrices: x y z X 1 2 3 4 4 6 8 = 10 2 1 0 -1 M = A To solve for x. D2 Maths HL The result suggests that for any two linear equations written in the form: ax + by = c dx + ey = f and there is a common difference in the constants a. such that: f-e = e-d but: (f-e) or (e-d) ≠ (c-b) or (b-a) because if the common difference in the two equations is the same. y and z we have to find the inverse of the matrix M. this means the determinant = 0. and multiply it with A: X = A M-1 Use technology to determine the inverse of M: This is a singular matrix. such that: c-b = b-a and a common difference in the constants d. and it will not be possible to solve for x and y. Therefore there are either many solutions for x. or there is no solution at all: . e and f. y and z. and therefore they will never intersect. this will suggest that the two lines are collinear.Kamal F Seif.

e. This shows that all 3 x 3 matrices with arithmetic progression will have a determinant of 0.P1b +2bc – 2bc) (U1 + d)(P1Q1 . In order to find out if there are no solutions we have to see if there is a contradiction in the equations: First the three are grouped in groups of two as shown: -+ .e. Let the first term of the first equation be U1 and the common difference d Let the first term of the second equation be P1 and the common difference be c Let the first tem of the third equation of be Q1 and the common difference b The equations will look like: U1 x + (U1 + d)y + (U1 + 2d)z = (U1 +3d) P1 x + (P1 + c)y + (P1 + 2c)z = (P1 + 3c) Q1 x + (Q1 + b)y + (Q1 + 2b)z = (Q1 +3b) Arranging the equation into a matrix: X y z U1 P1 Q1 (U1 +d) (P1 + c) (Q1 + b) (U1 + 2d) (P1 + 2c) (Q1 + 2b) = (U1 +3d) (P1 + 3c) (Q1 +3b) Finding the determinant: U1[(Q1+2b)(P1+c) – (Q1+b)(P1+2c)] – (U1+d)[P1(Q1+2b) – Q1(P1+2c)] + (U1+2d)[P1(Q1+b) – Q1(P1+c) U1(P1Q1 – P1Q1 + Q1c – 2Q1c + 2P1b .2P1U1b + 2Q1U1c . form a singular matrix. no definite answer. they intersect in a line. This means there is either a contradiction in the equations i.P1Q1 + 2P1b – 2Q1c) (U1 + 2d)(P1Q1 – P1Q1 + P1b – Q1c) 2P1U1b .Kamal F Seif.2Q1dc + 2P1bd . i.2P1bd = 0. i.e. or there are many answers. D2 Maths HL It seems that all 3 x 3 systems that exhibit an arithmetic progression will give a determinant of zero.2Q1U1c + 2Q1dc .

they intersect not at a point. Following the equation of the line: .Kamal F Seif.3U1c (p1d – U1c) y + (P1d – U1c) 2z = (P1d – U1c) 3 With the first two equations we find: Last two equations: P1Q1 x + P1Q1 y + Q1c y + P1Q1 z + 2Q1c z = P1Q1 + 3Q1c P1Q1 x + P1Q1 y + P1b y + P1Q1 z + 2P1bz = P1Q1 + 3P1b Q1c y – P1b y + 2Q1c z – 2P1bz = 3Q1c – 3P1b (Q1c – P1b) y + (Q1c – P1b) 2z = (Q1c – P1b) 3 y + 2z = 3 The two solutions show us that there is no contradiction in the three equations. but they intersect to form a line. If we plot the equations: x + 2y + 3z =4 4x + 6y + 8z = 10 2x + y = -1 subtract the second from the first.2U1c z = 3P1d . this means that the equation has many solutions. Multiply the first equation by P1 to eliminate x Multiply by U1 Multiply by Q1 to eliminate x Multiply by P1 we get the following graph: This shows us that the three equations join to make a line. i. D2 Maths HL U1 x + (U1 + d)y + (U1 + 2d)z = (U1 +3d) P1 x + (P1 + c)y + (P1 + 2c)z = (P1 + 3c) Q1 x + (Q1 + b)y + (Q1 + 2b)z = (Q1 +3b) First two equations: P1U1 x + P1U1 y + P1d y + P1U1 z + 2P1d z = P1U1 + 3P1d P1U1 x + P1U1 y + U1c y + P1U1 z + 2U1 z = P1U1 + 3U1c P1d y . Y + 2z = 3 subtract the second from the first.e.U1c y + 2P1d z .

1) and P2(0. The equation exhibits a geometric series with a common ratio of 2. if we take the first constant and multiply it by the common ratio we get the second constant and so on.e. we can use the two points to find the direction vector of the line. 1. The equations follow the general formula Un=U1rn-1 where: U1 is the first term of the series n is the term number (i. The second constant is two times the first. 2). (P2 – P1): Direction vector: 1 -2 1 Therefore we can say that for a 3 x 3 system that exhibit an arithmetic sequence. the three plains will meet to form a line that has the direction vector: 1 . D2 Maths HL Y + 2z = 3 when y=1. etc) r is the common ratio If we re-write the equations in the form of y = ax + b: y =− x + 2 y = 5x - . z=2. z=1. first. For second equation the constants are: 5 -1 The common ratio is − . Part B: Consider this 2 x 2 system: x + 2y = 4 5x – y = Examining the equations.e. i. third. and the third is two times the second. The point on the line has to -2 1 satisfy the equation: U1 x + (U1 + d)y + (U1 + 2d)z = (U1 +3d) where U1 is the first term of the arithmetic series and d is the common difference of the series. x=-1 when y=-1.Kamal F Seif. In the first equation the constants are: 1 2 4. second. x=0 We have two points P1(-1. -1. they exhibit a geometric series in the constants of the equations. or a multiple of it.

4 If we represent the lines on a graph we can determine the point of intersection of the two lines (point A): i. and a is the negative inverse of b.8 multiply the second equation by 5 to simplify it: multiply the first equation by 25 to eliminate x plugging in the value for y in our original equation: 5x = 25x – 9 = 1 25x = 10 x= ≈ 0. they are negative inverses of each other. . the solution for x and y.e. b is the negative inverse of a.Kamal F Seif.e. D2 Maths HL We see that the constants have a common feature. i. this means if we multiply the constant a by b the result is -1: 5 X − = -1 − X 2 = -1 Solving the two equations to get the values for x and y: x + 2y = 4 5x – y = x + 2y = 4 25x – 5y = 1 25x + 50y = 100 25x – 5y = 1 55y = 99 y= ≈ 1.

25) E:(0.P1U1v y = P1U1r2 .5) The solutions to the different lines can be calculated using the general formula: U1 x +U1r y = U1r2 P1 x + P1 v y = P1 v2 geometric series with first term U1 and common ratio of r geometric series with first term P1 and common ratio of v multiplied the first equation by P1 to eliminate x multiplied the second equation by U1 to eliminate x P1U1 x + P1U1r y = P1U1r2 P1U1 x + P1U1v y = P1U1v2 P1U1r y .1.rv To prove the formula for the x and y coordinates.3) F:(-10.-0.7) D:(-0.P1U1v2 P1U1 y (r – v) = P1U1 (r2 – v2) y= ( ( ) ) = ( ( )( ) ) = (r + v) when we plug in the value for y in our original equation: U1 x + U1r (r + v)= U1r2 U1 x = U1r2 .3) H:(1. the point of intersection for the lines: .4.7) G:( -1. (for point F on the graph).U1r(r + v) x = r2 –r(r + v) x =r2 –r2 – rv x = .8) B:(1.2.13.5.4.3.1.5.8) I:(2.1. D2 Maths HL A:(0.4.-0.Kamal F Seif.5) C:(-0.5.

(r + v)) Coordinate x= .rv. D2 Maths HL y=− x+2 y=− x+5 common ratio (r) = 2 common ratio (v) = 5 Therefore the point F (.(5 X 2) = -10 Coordinate y= 5 +2 = 7 Point F(-10. . 7) as seen from the graph. The same formula can be used to calculate the different points of intersection for the different graphs.Kamal F Seif.

- System of Linear EquationsUploaded byKomal Shujaat
- IA MathHL Type 1 - LasseUploaded byLasse Østebø Løvik
- IB HL Investigation Type I Patterns Within Systems of Linear EquationsUploaded bychirag2709
- MATH HL PORTFOLIO (APs and GPs)Uploaded byBenjamin Valiente
- IB Mathematics HL RevisionUploaded byDominic Summers
- Research Letter About ACT WritingUploaded byandernick
- Math ProjectUploaded byMariana Salazar Baquero
- Equatons of Straight LineUploaded byBilly Cheung